2016
DOI: 10.5455/ijmsph.2016.05032016379
|View full text |Cite
|
Sign up to set email alerts
|

Role of flexible fiber-optic bronchoscopy in the diagnosis of pulmonary diseases in rural-based tertiary hospital

Abstract: Background: Flexible fiber-optic bronchoscopy (FFB) is a well-established procedure in pulmonary medicine but still underutilized in rural area of developing countries where patients are still managed without confirmation of diagnosis. It is considered as an important tool in the diagnosis and therapy of varieties of pulmonary diseases. Objective: To study the role of bronchoscopy in diagnosis of different pulmonary diseases such as tuberculosis, pneumonia, and lung cancer. Materials and Methods: All consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In Kshatriya et al, diagnostic yield of bronchoscopy was 68% through BAL cytology, brush cytology and bronchoscopy guided biopsy. 10 Squamous cell carcinoma (44%) more common in this study as in our study adenocarcinoma was more common. Male were more common affected in this study as in our study also male were more common affected.…”
Section: Discussionsupporting
confidence: 54%
“…In Kshatriya et al, diagnostic yield of bronchoscopy was 68% through BAL cytology, brush cytology and bronchoscopy guided biopsy. 10 Squamous cell carcinoma (44%) more common in this study as in our study adenocarcinoma was more common. Male were more common affected in this study as in our study also male were more common affected.…”
Section: Discussionsupporting
confidence: 54%
“…There was no correlation between duration of asthma treatment and serum vitamin D3 level, grade of obstruction, FEV1 (%) predicted, and FEV1/FVC Ratio (%) were shows statistically significant corelation with vitamin D3 level. According to Nimit V. Khara et al [13],in 2016 conducted a study where total patients were divided into four groups that was <40 year 8(15.1%), 41-80 year in 12 (22.6%), 51-60 in 13 (24.5%), 61-70 in 14 (26.4%). In study by SN Jindal et al [14], in 2012 where 2.05% Patient are of > 15 year and 3.49 % adult aged ≥35 year.…”
Section: Resultsmentioning
confidence: 99%
“…In present study most common histological type is squamous cell carcinoma, followed by adenocarcinoma. While many studies showed squamous cell carcinoma is the most common type in lung malignancy (By Kshatriya et al, 15 Rabahi et al, 16 ), while other study shows adenocarcinoma is most common. (Bhavasar et al 13 ).…”
Section: Discussionmentioning
confidence: 96%
“…Similar Findings seen in many other studies. (By Bhavsar et al, 13 Kumar et al, 11 Kshatriya et al, 15 ). Aadenocarcinoma was more seen in female and non-smoker male.…”
Section: Discussionmentioning
confidence: 99%